The design of a structural Hyper-resisting element for Life Threatening Earthquake risk (SHELTER) for building collapse scenarios: The life-saving capsule. (1st May 2022) - Guerreiro, João; Gomes Ferreira, João; Guerreiro, Luís; Moura, Rita; Hosseini, Seyedsajjad
Highlights: An innovative approach to save lives in case of building collapse caused by earthquakes, to be adopted if overall building strengthening in inviable, was presented as a concept in a previous paper. The concept consists of installing a hyper-strong structural protection "capsule" where building occupants can be sheltered, after a seismic alarm is triggered, during building collapse and until rescue arrival. This paper presents the structural design of the protecting unit, based on methodologies specifically developed for the solicitations involved in the critical scenarios considered. Besides the unit strength, a damping system was conceived and designed that can reduced human body accelerations to bearable limits in case of building collapse. Abstract: The most severe seismic events normally cause the collapse of vulnerable buildings' leading to injuries and death of their occupants. Such catastrophic toll in death and injuries can be avoided based on an innovative approach currently underway, through the project SHELTER – Structural Hyper-resisting Element for Life Threatening Earthquake Risk (Ferreira et al., 2021), consisting on the development of a functional unit to protect the building occupants. Previous research found no relevant information about the ability of such kind of a structure to withstand the severity of building collapsing effects, while keeping the people inside it alive. The current work shows that there are chances of survival for those who occupy this shelter, as long as they settle over chairs equipped with a shock-absorber. The shelter will fall following the building collapse and will suffer several impacts with it, the most hazardous to be the last one, when it hits the ground. This shock-absorber system was designed so it could retrieve humanly tolerable accelerations, for different impact conditions, meaning different ground stiffness's and different impact positions. Two different criteria were used, one based in human tolerance curves (Eiband's curves) and another based directly on the compressive strength of the human spine. The shelter structural behaviour was also validated, through nonlinear time-history analyses of complete shelter models, for either the shelter fall from height, i.e., the building collapse when the shelter is installed in an upper floor, and for the building collapse when the shelter is installed on the ground floor and receives all the building rubble over it.